Value of HIV patients with regular follow‐up as In‐house Internal Controls of Flow Cytometry Measurement of Lymphocyte Subsets. Issue 5 (8th August 2013) - de, Marcelo; Kohler, Chantal; Henard, Sandrine; Rabaud, Christian; Béné, Marie C.; Faure, Gilbert C.; Béné, Marie C.; Marti, Gerald E.
<x xml:space="preserve">Abstract</x> Background Quality assessment in flow cytometry cannot obey the same rules as those applicable to the measurement of chemical analytes. However, regular follow‐up of known patients may provide a robust in‐house control of cell subsets evaluation. Methods Sequential blood samples assessed for 32 HIV patients over several years and showing good stability were retrospectively assessed to establish coefficient of variations of the percentages of CD3+, CD4+, CD8+ cells, and CD4+ absolute counts (ACs). Results Mean relative standard variations for the whole cohort were of 0.04, 0.14, 0.08, and 0.18 for CD3%, CD4%, CD8%, and CD4 ACs, respectively. Discussion In‐house follow‐up of regularly checked compliant patients is a good alternative to traditional and costly repeatability and reproducibility studies for the validation of routine flow cytometry. © 2013 International Clinical Cytometry Society